Butyrate Inhibits Gastric Cancer Cells by Inducing Mitochondriamediated Apoptosis - Zhang, Ke; Ji, Xiawei; Song, Zhengyang; Wu, Fangquan; Qu, Yue; Jin, Xiaofeng; Xue, Xiangyang; Wang, Fangyan; Huang, Yingpeng (Combinatorial Chemistry & High Throughput Screening, 2023)
Background: Gastric cancer (GC) remains a common cause of cancer death in East Asia. Current treatment strategies for GC, including medical and surgical interventions, are suboptimal. Butyrate, a short-chain fatty acid produced by the intestinal flora, has been reported to be able to inhibit gastric carcinogenesis. This study aimed to investigate the effects of butyrate on human GC and its underlying mechanisms. Materials and Methods: Human GC cell lines BGC-823 and SGC-7901, human GC tissues and adjacent normal tissues were used for this study. Cell proliferation was assessed using CCK-8 and EdU staining. TUNEL fluorescence and Annexin V/PI staining were adopted for qualitative and quantitative evaluation of cell apoptosis, respectively. Reactive oxygen species (ROS) assay was performed to analyse mitochondrial function. Real-time q-PCR and western blot were carried out to examine the expression of apoptosis-related genes and the synthesis of apoptosis-related proteins. The association between G protein-coupled receptor 109a (GPR109a) and GC prognosis was analyzed using data from The Cancer Genome Atlas (TCGA). Results: CCK-8 and EdU staining confirmed inhibitory activities of butyrate against human GC cells. Annexin V/PI staining and TUNEL fluorescence microscopy showed that butyrate promoted GC cell apoptosis. No difference in the expression of GPR109a was found between GC tissues and adjacent normal tissues, and no direct association between GPR109a and GC prognosis was discovered, suggesting that GPR109a may not be a key factor mediating the apoptosis of GC cells. Butyrate increased the synthesis of caspase 9 and decreased BCL-2, the well-known effector and regulator of mitochondria-mediated apoptosis, and significantly induced mitochondrial ROS. Conclusion: Collectively, our results suggest that butyrate is able to inhibit the proliferation of GC cells and induce GC apoptosis, possibly via a mitochondrial pathway.
Keywords: gastric cancer